Optimization of Output Characteristics in Figure-9 Mode-Locked Fiber Laser Based on Black Phosphorus Assistance - Peiyuan Xiao; Lu Sui; Wanzhuo Ma; Renshun Pan; Huilin Jiang (Photonics, 2025)
Utilizing the nonlinear effects of black phosphorus (BP), the self-starting threshold and noise performance were optimized in a figure-9 mode-locked fiber laser configuration. Experimental results demonstrate that a mode-locked pulse output with a spectral bandwidth of 8.2 nm, center wavelength of 1033.5 nm, and repetition rate of 42 MHz is obtained. Compared with single-mechanism mode-locked lasers, the self-starting mode-locked threshold is reduced by 100 mW. Regarding noise characteristics, the signal-to-noise ratio (SNR) is enhanced to 68.4 dB and the phase noise is reduced to −115.6 dBc/Hz at 1 MHz to 10 MHz frequency offsets. The root mean square (RMS) of the output power is optimized to 0.9% and phase noise jitter is reduced to 1.9%. This work proves a novel approach to tackle the challenges of high self-starting thresholds and instability in mode-locked lasers.